Smart Financial: Cerdas Merencanakan Keuangan di Era Digital - Ardiana, Meta; Pertiwi, Dwi Ari; Agustina, Rachma; Humaidi, Humaidi; Haryanti, Peni; Hidayati, Athi’; Mufarrihah, Iftitaahul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The era of digitalization has drastically changed the current business landscape. Digital marketing platforms, e-commerce, digital payments and digital financial services (FinTech) have become an inseparable part of modern business operations. The rapid development in the digital world of various financial applications and software is here to help business actors in managing business finances, however there are still many business actors who make less than optimal use of it due to limited education, resources, knowledge and skills. This community service is designed to increase digital financial literacy among parents of SDN Selopanggung I students, most of whom are self-employed. Their business is in the field of rosella farming and processing. This training succeeded in showing that good financial recording and management is the main foundation for business continuity, no matter how small the business scale. This change is reflected in the increased motivation of participants in recording business accounting as well as periodically comparing business performance and utilization of digital financial services.